REAL INVESTMENT PROCESSES AND ACCELERATION OF TERRITORIAL ECONOMIC DEVELOPMENT - Juraev Elyorbek Sobirjon ogli (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article analyzes the directions of real investment processes in Namangan region and their role in accelerating economic development.